Implementasi Metode Copras Dan Pembobotan ROC Dalam Seleksi Penerimaan Bantuan Sosial (BANSOS) Di Kelurahan Delitua Barat - Larosa, John Steven (STMIK Budi Darma, 2024)
One of the government programs at the West Delitua subdistrict office is social assistance assistance. The distribution of aid must be carried out transparently or by family card so that the aid provided is received by less fortunate people directly. Many underprivileged families will be selected conventionally, which is feared to result in inaccuracies in assessing or selecting objectively, which could result in social assistance assistance not being distributed to people who are truly incapacitated and could result in inaccuracies. This problem can be corrected by building a decision support system, namely the Complex Proportional Assessment (COPRAS) method. It is hoped that this application can help the West Delitua subdistrict office in making decisions quickly, precisely and fairly. This application requires alternative data and features. The system will provide an